2018
DOI: 10.1016/j.apsusc.2017.09.222
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonic acid functionalization of nanostructured Ni–W coatings on steel

Abstract:  Robust and stable octadecylphosphonic acid self-assembled layers on nanostructured Ni-W coatings on steel were obtained by thermal annealing.  XPS, Raman, contact angle and electrochemical measurements confirm the functionalization and characteristics of the phosphonic layer.  The functionalized Ni-W samples exhibit high hydrophobicity and corrosion resistance in chloride containing solutions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…Such decrease (-0.64 to -0.89 eV) of binding energy of P can be explained by the creation of a covalent bond with surface Ti-OH groups. Similar shifts between P 2p3/2 signal in free and bonded octadecylphosphonic acid were reported for the grafting on the surface of TiO2 (-0.2 eV [52]), Ta2O5 (-0.5 eV [53] and Ni-W (-0.8 eV [54]).…”
Section: Phosphonation Experimentssupporting
confidence: 79%
“…Such decrease (-0.64 to -0.89 eV) of binding energy of P can be explained by the creation of a covalent bond with surface Ti-OH groups. Similar shifts between P 2p3/2 signal in free and bonded octadecylphosphonic acid were reported for the grafting on the surface of TiO2 (-0.2 eV [52]), Ta2O5 (-0.5 eV [53] and Ni-W (-0.8 eV [54]).…”
Section: Phosphonation Experimentssupporting
confidence: 79%
“…Fine aggregates are gathered near the edges of the grains, which can be ascribed to the diamond particles. Unlike nodular shapes of the grains of the Ni–W [30] , [31] , Ni-Co [32] , [33] matrix, the Ni/diamond shows pyramids-like grains. It indicated that more diamond particles aggregated when the coatings were deposited with magnetic stirring.…”
Section: Resultsmentioning
confidence: 89%
“…As the W content increases from 2.51% to 45.29%, the hardness of the coating enhances from 383.3 HV to 437.5 HV, indicating that the hard tungsten contributes to the hardness of coatings [36,37]. The study shows that when the content of W in the coating increases, the degree of lattice distortion of the alloy increases, and the resistance of dislocation movement also increases, which leads to the increase of the micro-hardness of the alloy [38,39].…”
Section: The Micro-hardness Of Ni-w Graded Coatingsmentioning
confidence: 82%